Spectroscopic Study of the Interaction between Horse Heart Myoglobin and Zirconium(IV)‐Substituted Polyoxometalates as Artificial Proteases. Issue 18 (3rd August 2017) - Ly, Hong Giang T.; Parac‐Vogt, Tatjana N.
Abstract: A recent study [ Angew. Chem. Int. Ed .2015, 54, 7391–7394] has shown that horse heart myoglobin (HHM) is selectively hydrolyzed by a range of zirconium(IV)‐substituted polyoxometalates (POMs) under mild conditions. In this study, the molecular interactions between the Zr‐POM catalysts and HHM are investigated by using a range of complementary techniques, including circular dichroism (CD), UV/Vis spectroscopy, tryptophan fluorescence spectroscopy, and 1 H and 31 P NMR spectroscopy. A tryptophan fluorescence quenching study reveals that, among all examined Zr‐POMs, the most reactive POM, 2:2 Zr IV ‐Keggin, exhibits the strongest interaction with HHM. 31 P NMR spectroscopy studies show that this POM dissociates in solution, resulting in the formation of a monomeric 1:1 Zr IV ‐Keggin structure, which is likely to be a catalytically active species. In the presence of Zr IV ‐POMs, HHM does not undergo complete denaturation, as evidenced by CD, UV/Vis, tryptophan fluorescence, and 1 H NMR spectroscopy. CD spectroscopy shows a gradual decrease in the α‐helical content of HHM upon addition of Zr IV ‐POMs. The largest effect is observed in the presence of a large Zr IV ‐Wells–Dawson structure, whereas small Zr IV ‐Lindqvist POM has the least influence on the decrease in the α‐helical content of HHM. In all cases, the Soret band at λ =409 nm is maintained in the presence of all examined Zr‐POMs, which indicates that no conformational changes in the protein occur near the heme group. Abstract : Probing the heart of the complex : The interaction between horse heart myoglobin and zirconium(IV)‐substituted polyoxometalates (POMs) is revealed through spectroscopic techniques including circular dichroism, UV/Vis, tryptophan fluorescence, 1 H NMR, and 31 P NMR spectroscopy (see figure).